(untitled) (Czech Journal of International Relations, 1966)
The search for alternatives can be called the current situation that appears in the ever-increasing period of US foreign policy towards the number of publications, articles and European socialist countries. Most of them are based on a clear conviction about the necessity of changes in American foreign policy in this area. Among the authors we can find many people who have cooperated or are still cooperating with the State Department or other American government agencies. John C. Campbell in his book American Policy toward Eastern Europe, The Choices Ahead devotes a significant part to describing the historical development in Eastern Europe, especially after the Second World War, taking into account American policy. It is based on the fact that the destinies of these countries became the center of American interest only after the Second World War, and that, as he states, as the subject of "a kind of American domestic politics, kicked up once every three years during presidential elections". When these countries are a welcome target of anti-communist attacks of the country is especially trying to analyze the place of Poland and Yugoslavia in American foreign policy. Even if the author largely agrees with the goals that American foreign policy pursues in European socialist countries (hopes for changes in the social system, increased conflict with the USSR through the rise of nationalism), a number of critical comments on current policy can be found in his work.